Radiographic evaluation of the effect of obesity on alveolar bone in rats with ligature-induced periodontal disease - do Nascimento CM (Dove Medical Press, 2013)
Cassiane Merigo do Nascimento,1 Tiago Cassol,2 Fernanda Soares da Silva,3 Maria Lucia Bonfleur,4 Carlos Augusto Nassar,5 Patricia Oehlmeyer Nassar5 1Biologica Science and Health Center, State University of West Paraná (UNIOESTE), Cascavel, Paraná, Brazil; 2State University of West Paraná (UNIOESTE), Cascavel, Paraná, Brazil; Department of 3Pharmacy, 4Fisiology, 5Periodontology, Dental School, State University of West Paraná (UNIOESTE), Cascavel, Paraná, Brazil Abstract: There is evidence that the lack of metabolic control of obese patients may accelerate periodontitis. The aim of this study was to evaluate radiographically the effect of cafeteria-diet-induced obesity on alveolar bone loss in rats subjected to periodontal disease. Twenty male Wistar rats were randomly divided into four groups: 1) control group, 2) control and ligature group; 3) cafeteria group; and 4) cafeteria and ligature group. The animals were evaluated for obesity and euthanized, and the mandible of each rat was removed to perform a radiographic evaluation of alveolar bone loss and its effect on diet-induced obesity. The results showed greater alveolar bone loss in the mice in Group 4 (P<0.01). Thus, we concluded that obese mice, on average, showed greater radiographic evidence of alveolar bone loss than mice undergoing induction of obesity. Keywords: periodontal disease, radiography, obesity